Comparative Study on Effectiveness and Safety of Atorvastatin with Rosuvastatin in Hyperlipidemic Patients at a Tertiary Care Hospital in Nepal - Raut, Binod; Paudel, Nimesh; Shrestha, Deepti; Bhosekar, Anant (Journal of Institute of Medicine Nepal, 2020)
Introduction Hyperlipidemia is one of the most contributing factors to coronary heart diseases. Statins have become standard medicine in clinical practice to reduce total cholesterol, low density lipoprotein and to increase high density lipoprotein cholesterol. This study is conducted to compare the effectiveness and safety of atorvastatin with rosuvastatin in hyperlipidemic patients.MethodsThis is a prospective observational study involving 150 patients conducted in the Department of Internal Medicine of Kathmandu Medical College and Teaching Hospital from July 2019 to March 2020. Patients newly diagnosed with hyperlipidemia were enrolled. Patients that were prescribed with 10 mg of atorvastatin and 5 mg of rosuvastatin by the treating physician once daily for 6 weeks were divided into two groups. Data was recorded in the customized proforma and the SPSS package version 20 was used for analysis.ResultsPatients that were prescribed with atorvastatin were put in group I and those prescribed with rosuvastatin were included in group II with 75 participants in each group. The mean age of the patients were 50.56± 10.08 years in group I and 52.45±10.20 years in group II with male to female ratio of 3:1. The mean BMI of group I was 25.36±1.74 and that of group II was 26.48±2.21 before therapy. There was a significant main effect of duration (F1,74=401.02, p